Petrology, Age, and Rift Origin of Ultramafic Lamprophyres (Aillikites) at Mount Webb, a New Alkaline Province in Central Australia - Z. J. Sudholz; T. H. Reddicliffe; A. L. Jaques; G. M. Yaxley; M. Haynes; A. Gorbatov; K. Czarnota; C. Frigo; R. Maas; B. Knowles (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Diamond exploration over the past decade has led to the discovery of a new province of kimberlitic pipes (the Webb Province) in the Gibson Desert of central Australia. The Webb pipes comprise sparse macrocrystic olivine set in a groundmass of olivine, phlogopite, perovskite, spinel, clinopyroxene, titanian‐andradite and carbonate. The pipes resemble ultramafic lamprophyres (notably aillikites) in their mineralogy, major and minor oxide chemistry, and initial 87Sr/86Sr and εNd‐εHf isotopic compositions. Ion probe U‐Pb geochronology on perovskite (806 ± 22 Ma) indicates the eruption of the pipes was co‐eval with plume‐related magmatism within central Australia (Willouran‐Gairdner Volcanic Event) associated with the opening of the Centralian Superbasin and Rodinia supercontinent break‐up. The equilibration pressure and temperature of mantle‐derived garnet and chromian (Cr) diopside xenocrysts range between 17 and 40 kbar and 750–1320°C and define a paleo‐lithospheric thickness of 140 ± 10 km. Chemical variations of xenocrysts define litho‐chemical horizons within the shallow, middle, and deep sub‐continental lithospheric mantle (SCLM). The shallow SCLM (50–70 km), which includes garnet‐spinel and spinel lherzolite, contains Cr diopside with weakly refertilized rare earth element compositions and unenriched compositions. The mid‐lithosphere (70–85 km) has lower modal abundances of Cr diopside. This layer corresponds to a seismic mid‐lithosphere discontinuity interpreted as pargasite‐bearing lherzolite. The deep SCLM (>90 km) comprises refertilized garnet lherzolite that was metasomatized by a silicate‐carbonatite melt.